Quantum Information Concepts in Open Quantum Systems - Vacchini, Bassano; Smirne, Andrea; Megier, Nina (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This issue contains contributions in different cutting edge topics within the field of open quantum systems. The theoretical work presented is focused, in particular, on quantum thermodynamics and quantum non-Markovianity and provides a window into current research in these fields. Different perspectives are considered that share a common root in the exploitation of open quantum systems and quantum information tools.